Caracterização de resistência a antimicrobianos de isolados clínicos de Acinetobacter calcoaceticus-baumannii - Rodrigues, Belisa Avila (2016)
Acinetobacter calcoaceticus-baumannii (ACB) are opportunistic pathogens responsible for respiratory tract infections, wound infections, and bacteremia in intensive care units patients. These microorganisms became a problem in health care units due to their ability to acquire and accumulate resistance determinants. They are resistant to important antibiotics commonly used to treat infections caused by them. Thus, this study aimed to determine the antimicrobial susceptibility and detect resistance determinants in clinical ACB isolates. For this, 200 clinical ACB isolates, resistant to carbapenems, were collected from a hospital in Porto Alegre, Brazil. To determine susceptibility to antimicrobial agents, 16 antimicrobials were used in the disk diffusion technique and the minimum inhibitory concentration (MIC) for polymyxin B and meropenem was performed by broth microdilution. Additionally, MIC for polymyxin B in 17 isolates was determined using different methods in comparison with broth microdilution, adopted as reference method. The presence of blaOXA-23, blaOXA-51, blaIMP and blaNDM, as well as class 1 and 2 integrons, were detected by PCR. A total of 82.5% were extremely resistant (XDR) and 17.5% were multidrug resistant (MDR). Forty-six non-susceptibility patterns were found among the isolates, with polymyxins, tetracyclines, and aminoglycosides being the classes with higher rate of susceptibility. When different methods to determining MIC for polymyxin B were evaluated, very major errors and major errors were found in E-test and major errors in agar dilution, as compared with the reference method. The broth microdilution with polysorbate 80 showed a reduction of two or more dilutions in most isolates (82.3%). The blaOXA-23 and blaOXA-51 genes were found in 100% of the isolates, while 49% harbored blaIMP. The blaNDM gene was not found in any isolate. Class 1 and class 2 integrons were found in 68% and 88% of the isolates, respectively. The high percentage of XDR isolates, as well as the detection of important resistance determinants and the high rate of integrons found, reinforce the concern regarding ACB microorganisms and their spread in health care units.